2011
DOI: 10.1515/jbcpp.2011.024
|View full text |Cite
|
Sign up to set email alerts
|

Left anterior descending/right coronary artery as culprit arteries in acute myocardial infarction (n=2011) in changing physical environment, percutaneous coronary intervention data, 2000–2010

Abstract: High daily neutron activity and low GMA are accompanied by increasing LAD as a culprit artery in AMI. The possible mechanisms of this finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The results of this study support previous cosmobiological research, which generally pointed to a link between cardiac events such as cardiac arrhythmias, sudden cardiac death, acute myocardial infarction, and cerebral stroke with levels of cosmic ray, solar, and geomagnetic activity . Our study also extends these findings to the most dangerous form of cardiac arrhythmia‐electric heart storms, showing a significant relationship between the time of occurrence of electrical heart storms detected by implanted defibrillators and relatively high levels of cosmic ray (neutron) activity.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study support previous cosmobiological research, which generally pointed to a link between cardiac events such as cardiac arrhythmias, sudden cardiac death, acute myocardial infarction, and cerebral stroke with levels of cosmic ray, solar, and geomagnetic activity . Our study also extends these findings to the most dangerous form of cardiac arrhythmia‐electric heart storms, showing a significant relationship between the time of occurrence of electrical heart storms detected by implanted defibrillators and relatively high levels of cosmic ray (neutron) activity.…”
Section: Discussionsupporting
confidence: 90%
“…If we extrapolate the Neutron action as it's accepted in radiotherapy [55] [56], we can presume that Neutron biological action is related with Neutrons are connecting with the H + anion (that is in high concentration in some lipid tissues and atheromatous plaques), converting to Protons, acting as damaging subject on cells and tissues, especially in damaged heart muscle, lipid infiltrated arterial walls, heart conduction system [54] [55]. The possible shield by the magnetic field from high Neutron activity in AMI and SCD was confirmed in a number of recent studies [28]- [30] and in a big international study of Mayo clinic (USA, Italy, Czech Republic [32]) that confirmed previous observations about inverse relationship of GMA with life threatening cardiac arrhythmia, [47] [54] and, also, at days of electrical hearts storms, when life threatening arrhythmias occurred three and more times daily (and also treated by implanted electrical defibrillators). The role of cosmic rays in physics and human life is widely discussed in recent publications [51] [57]- [59].…”
Section: Discussionmentioning
confidence: 96%
“…In many places the weather prediction reports include GMA Stormy days. In the last years it was established that GMA is correlated with Solar Activity (SA) by r = 0.55, p < 0.0001 and the both are inverse related to Cosmic Ray activity (CRA) (expressed by Neutron Activity by the Earth's surface in impulse/minute (imp/min)-SA/CRA r = −0.85 -−0.86, p < 0.0001; GMA/CRA = −0.66, p < 0.0001 [30] [34]…”
mentioning
confidence: 99%
“…The presented data demonstrated the possible effects of high CRA (neutron activity) on a number of human pathologies, and mortality in general. In three studies of other groups with participation of authors, published recently, it was shown: 1) a significant rise of admissions for AMI on days following the days with "Zero" GMA levels, mostly on the first and second days at 23% and prolonged until the 6-th day after the "Zero" GMA level day [48,49]; 2) rising lesions in the Left Anterior Descending Coronary Artery (LAD)-the most serious lesion among the three coronary arteries-concomitant with drop of GMA level by 28% in I 0 level GMA days compared to IV 0 GMA days and achieving 62% rise at days of "Zero" GMA level [50].…”
Section: Discussionmentioning
confidence: 99%
“…Inverse correlation of GMA with CRA (neutron activity) (r = −0.66, p < 0.0001) and CRA (neutron activity) with solar activity are similar (r = −0.85) [49][50][51]. The last relationship explains the much higher frequency of zero GMA on the lower part of the 11-year solar activity cycle.…”
Section: Discussionmentioning
confidence: 99%